Application of Arduino-Based Systems as Monitoring Tools in Indoor Comfort Studies: A Bibliometric Analysis - Daniel Trento; Ticiana Patel Weiss Trento; Eduardo Krüger (International Journal of Architectural Engineering Technology, 2020)
Studies that require environmental measurements often struggle with the cost of monitoring equipment. Costs will increase as more variables are required. Thus, scientists have been increasingly relying on Arduino systems to overcome such a challenge. This paper aims to review the literature on the use of Arduino as a viable measurement tool in indoor comfort research. For this purpose, the results from three databases were compared: Web of Science, Scopus and ScienceDirect. Results from the Scopus search were then analyzed using VOSViewer according to three questions: (1) what is the state of the art and trends using Arduino; (2) how is Arduino being used in indoor environments; and (3) which are the main authors using the system and what are the most cited Arduino-related sources. The maps showed that the system is very versatile and offers the opportunity to strengthen multidisciplinary approaches.